Tourism demand analysis of Chinese arrivals in Thailand - Akarapong Untong (2018)
This paper analyses Chinese tourist arrivals in Thailand during the last 25 years using various quantitative techniques. The number of Chinese tourists in Thailand has been increasing for two decades but since 2009 the trend has been particularly dramatic, with a 56.84% annual growth rate. The study found an increase of seasonality, but arrivals showed the same yearly pattern. Income elasticity indicates that Thailand will continue to benefit from China's economic growth. In addition, Chinese tourists respond less to a change in Thailand's prices than to changes in competitors' prices. In 2017, Chinese arrivals are forecast to reach 7.9 million with an annual growth rate of 19.98% since 2013. Therefore, Thailand should focus on capacity preparation for this market growth while monitoring the policies of its major competitors in the China outbound market.